NIKAH SIRRI DALAM PERSPEKTIF HADIS - Iballa, Dona Kahfi. Ma. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
This paper will discuss the issue of sirri marriages through the perspective of hadith. To give a holistic understanding of the problem regarding the hadith prohibiting sirri marriages and those instructing for the recording of marriages, this paper will utilize the Maani al-Hadith method. The various Hadiths found on sirri marriages have found two important points. First, the prophet has instructed that as a legally binding relation recommended by religion, marriage must be different from other forms of relations prohibited by religion, in the form of publications. Second, the hadith, which are strengthened by Quranic verses also instructs that while the use ofÂ witnesses is sufficient for the legality of a marriage, if there are several requirementsÂ which are lacking in certain situations, a record or publication of the marriage must be made to avoid future dispute (a record of the marriage is the most effective method espoused by the Quranic verse).Â Furthermore, several other facts also become the basis for the mandatory nature of a marital record: 1) that marriages encompass not only legal, but also religious and social factors, 2) marital records protects not only from adultery, but also minimalizes the possibility for other future sins, and 3) that the existence of marital records is a characteristic of an upstanding Muslim following government laws.